LITERATURE REVIEW: USE OF TRANSCRIPTION TECHNOLOGY TO IMPROVE LEARNING ACCESSIBILITY FOR DEAF CHILDREN - Bhanasya shafa Aurelia (Journal of Disability, 2025)
This article is a literature review which aims to explore the use of transcription technology as a means of increasing learning accessibility for deaf children. Deaf children face obstacles in accessing written language due to their hearing limitations. Transcription technology can be an effective solution in overcoming this obstacle. Utilization of transcription technology allows deaf children to access written texts through text-to-speech transcription or display of translated text. In this article, we discuss several important aspects related to the use of transcription technology, including increasing understanding and involvement of deaf children in learning, developing language skills, accessibility to digital learning materials, and inclusion of deaf children in the wider educational environment. In this literature review, research results related to this topic have been summarized and identified the benefits and challenges associated with the use of transcription technology in the context of learning for deaf children. It is hoped that the results of this literature review will provide a better understanding of the importance of using transcription technology in increasing the accessibility of written language for deaf children. The practical implications of this article can help educators, technology developers, and other related parties in designing and implementing more inclusive solutions for the learning of deaf children